2017
DOI: 10.24193/jmr.28.2
|View full text |Cite
|
Sign up to set email alerts
|

Third-person Perception and Its Predictors in the Age of Facebook

Abstract: Originally proposed by Davison (1983), the TPE hypothesis maintains that people who are exposed to general persuasive media messages believe that these messages have a greater impact on others (i.e., "the third persons") than on themselves. Although classic TPE studies have long focused on the traditional mass media, many studies show that this effect is also common with regards to newer media outlets. By means of a survey (N=688), this study seeks to explore (1) the link between TPE and new mediums of communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
1
7
0
2
Order By: Relevance
“…This study examines the TPE of fake news on social media and how such a TPP of fake news associated with individual attitudes and behavioral intentions. Consistent with the extant literature regarding TPE and social media (Buturoiu et al, 2017; Lev-On, 2017; Schweisberger et al, 2014), we also found the “self-other” asymmetries in perceiving the influence of fake news on social media. Driven by the psychological need for self-enhancement (Perloff, 2002), individuals are, consciously or not, more inclined to project a greater effect of fake news on others than on themselves.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study examines the TPE of fake news on social media and how such a TPP of fake news associated with individual attitudes and behavioral intentions. Consistent with the extant literature regarding TPE and social media (Buturoiu et al, 2017; Lev-On, 2017; Schweisberger et al, 2014), we also found the “self-other” asymmetries in perceiving the influence of fake news on social media. Driven by the psychological need for self-enhancement (Perloff, 2002), individuals are, consciously or not, more inclined to project a greater effect of fake news on others than on themselves.…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of TPE has been frequently identified on various media (Sun et al, 2008) such as the internet (Antonopoulos et al, 2015; Chen & Ng, 2016), and social media (Buturoiu et al, 2017; Lev-On, 2017; Schweisberger et al, 2014), all of which pointed to the self-other asymmetries when it comes to gauging media effects. This “perceptual fallacy” often dictates the formulations of our perceptions, particularly our judgments of bias and objectivity (Pronin et al, 2004).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…More recently, studies are beginning to explore TPE in the context of Facebook use. By means of a survey with 688 participants, Buturoiu et al (2017) found that the more users perceived the influence of Facebook content as undesirable, the more they evaluated the effects of such content as being greater on others than on themselves.…”
Section: The Perceptual Component Of the Tpementioning
confidence: 99%
“…According to Buturoiu, Durach, Urdrea, and Corbu (2017) the third-person effect is greater when media content is seen as negative. Therefore, if a person perceives a message as overall good, and it supports their pre-held notions, they are less likely to have third-person effect (Buturoiu, Durach, Udrea, & Corbu, 2017).…”
Section: Third-person Effectmentioning
confidence: 93%
“…Therefore, it is important to know why a person chooses to accept a message because it will play a role in determining if they believe others will influence by a message. People are then more susceptible to messages if they have a vested interest or see the information as positive to their overall self-image and belief system (Buturoiu, Durach, Udrea, & Corbu, 2017). An example would be if someone received a message that supported already held beliefs and attitudes about their political party or religion.…”
Section: Third-person Effectmentioning
confidence: 99%